Evaluation of deformity and hand function in cerebral palsy patients - Wang Kwan; Gudushauri Paata; Yan Lam; Fung Boris; Lee Ellen Y; Law Karlen; Ip Josephine; Chow Shew (Journal of Orthopaedic Surgery and Research, 2008)
Abstract Background A cross-sectional study was performed to describe the upper limb deformity and function in cerebral palsy patients and to determine the correlation of deformity, spasticity, motor control, and sensation to hand function in the said population. Materials and methods Thirty patients satisfying our inclusion criteria underwent physical, sensory, and functional assessment using a standard protocol. Physical assessment included documentation of the degree of spasticity, deformity and muscle control. Sensation was tested using static two-point discrimination test and stereognosis test. Melbourne Assessment of the Unilateral Upper Limb Function Test (MAULF), Functional Hand Grip Test (FHGT), and Functional Independence Measure for children (WeeFIM) were used to evaluate hand function. Deformity, spasticity, motor control, and sensation were analyzed for correlation with hand function using Pearson Correlation analysis. A p-value of less than 0.05 was considered statistically significant. Results Functional deficits of the hand increased with increasing severity of deformity and spasticity. Tetraplegics were most affected by spasticity, deformity, poor motor control, sensory and functional deficits. Triplegics, followed by diplegics had more functional upper limbs in terms of the MAULF and FHGT scores. Unilaterally affected patients (triplegics and hemiplegics) scored better in performance of activities of daily living. The MAULF and FHGT had a stronger correlation to deformity, spasticity and motor control compared to the WeeFIM. Conclusion The degree of deformity, spasticity, sensory deficit, and motor control affected the hand function of a cerebral palsy patient significantly. The MAULF and FHGT more accurately represents hand function deficit in cerebral palsy patients.